Tests of conspecificity for allopatric vectors: Simulium nodosum and Simulium shirakii (Diptera: Simuliidae) in Asia - Van Lun Low (2018)
© 2015 Low et al. Background: Allopatric populations present challenges for biologists working with vectors. We suggest that conspecificity can be concluded in these cases when data from four character sets - chromosomal, ecological, molecular, and morphological - express variation no greater between the allopatric populations than between corresponding sympatric populations. We use this approach to test the conspecificity of Simulium nodosum Puri on the mainland of Southeast Asia and Simulium shirakii Kono & Takahasi in Taiwan. The validity of these two putative species has long been disputed given that they are morphologically indistinguishable. Findings: The mitochondria-encoded cytochrome c oxidase subunit I (COI), 12S rRNA, and 16S rRNA genes and the nuclear-encoded 28S rRNA gene support the conspecific status of S. nodosum from Myanmar, Thailand, and Vietnam and S. shirakii from Taiwan; 0 to 0.19 % genetic differences between the two taxa suggest intraspecific polymorphism. The banding patterns of the polytene chromosomes of the insular Taiwanese population of S. shirakii and mainland populations of S. nodosum are congruent. The overlapping ranges of habitat characteristics and hosts of S. nodosum and S. shirakii corroborate the chromosomal, molecular, and morphological data. Conclusions: Four independent sources of evidence (chromosomes, DNA, ecology, and morphology) support the conspecificity of S. nodosum and S. shirakii. We, therefore, synonymize S. shirakii with S. nodosum. This study provides a guide for applying the procedure of testing conspecificity to other sets of allopatric vectors.